CSR inhibiting factors in Student Start-up Business - Iswari, Hanif Rani; Sudarmiatin, Sudarmiatin; Hermawan, Agus (GOVERNORS, 2022)
The purpose of this study is to investigate the factors inhibiting CSR in student start-up businesses in Malang. Startups are businesses that are currently skyrocketing even though the storm of startup layoffs has started recently. This startup business is dominated by many young people with brilliant business ideas. Malang City, which is an education city, also has a growth in start-up businesses, one of which is dominated by young people who are still studying in higher education. Running a start-up business for business people who are still studying is not without obstacles. One of them is about their business activities related to social responsibility. This research is a quantitative approach with a survey method on student start-up businesses in Malang. The sample population taken was 128 respondents. Questionnaires are distributed using a likert scale. Data analysis uses SmartPLS version 3 to determine the confirmatory analysis. The findings of this study obtained CSR inhibiting factors for student startups in Malang are the lack of availability CSR information and knowledge, lack of availability of resources, lack of time availability of CSR activities and the level of awareness and benefits of CSR for companies. In addition, obstacles are also obtained from employee commitment to CSR. There are five CSR obstacles faced by student startups in Malang City.